2022
DOI: 10.1021/acs.accounts.2c00080
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte Effects on CO2 Electrochemical Reduction to CO

Abstract: Conspectus The electrochemical reduction of CO 2 (CO2RR) constitutes an alternative to fossil fuel-based technologies for the production of fuels and commodity chemicals. Yet the application of CO2RR electrolyzers is hampered by low energy and Faradaic efficiencies. Concomitant electrochemical reactions, like hydrogen evolution (HER), lower the selectivity, while the conversion of CO 2 into (bi)carbonate through solution acid–base reactions induces an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
127
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(159 citation statements)
references
References 78 publications
2
127
0
Order By: Relevance
“…To understand the product selectivity of a manganese polypyridyl catalyst between CO, H 2 , and HCO 2 H is challenging as it is dependent upon not only the ligand structure but also the applied potential, electrolyte solvent, p K a of the proton source used (or generated in situ), and mass-transfer diffusion rates of both CO 2 and the proton source . Prior heterogeneous studies by Reuillard et al.…”
Section: Resultsmentioning
confidence: 99%
“…To understand the product selectivity of a manganese polypyridyl catalyst between CO, H 2 , and HCO 2 H is challenging as it is dependent upon not only the ligand structure but also the applied potential, electrolyte solvent, p K a of the proton source used (or generated in situ), and mass-transfer diffusion rates of both CO 2 and the proton source . Prior heterogeneous studies by Reuillard et al.…”
Section: Resultsmentioning
confidence: 99%
“…DFT). [24][25][26]46 Thus, to date there has remained a disconnect between the sub-elds of mechanistic investigation and practical cell development. Our results highlight the importance of quantifying (and ideally controlling) the movement of cations from anolyte to MEA cathodes.…”
Section: Resultsmentioning
confidence: 99%
“…(iii) tuning the local electric eld. [24][25][26] An experimental-theoretical study by Resasco et al highlighted the essential role of cations in facilitating the C-C coupling step, and hence enhancing the selectivity towards C 2+ products. 50 They reported higher C 2+ production rates in the presence of heavier alkali cations attributing to their higher concentration (due to more compact hydrated radius) compared to the lighter ones in the outer Helmholtz plane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent study has reported that the electrolyte cation affects the activity of CO2 reduction reaction in the following order: Li + <Na + <K + <Cs + . 119 The roles of electrolyte cation in modulating the structure, conductivity and stability of POMs are rarely reported.…”
Section: Discussionmentioning
confidence: 99%